PENGARUH SELF EFFICACY, WORK LIFE BALANCE DAN QUALITY OF WORK LIFE TERHADAP KINERJA KARYAWAN KONTRAK DI HOTEL JAVA HERITAGE - Alldho Dharma Rahardhiansyah; Hermin Endratno; Akhmad Darmawan; Ika Yustina Rahmawati (ITB AAS Indonesia Surakarta, 2026)
his study addresses the issue of employee performance in the hospitality industry, which is determined not only by technical proficiency but also by psychological elements and work-related circumstances. The objective of this research is to analyze the effect of self- efficacy, work-life balance, and quality of work life on employee performance at Java Heritage Hotel Purwokerto. This study employs a quantitative approach using a census sampling technique involving all 110 employees of the hotel. Data collection relied on a structured questionnaire in which items were measured using a five point Likert scale. The collected data were analyzed utilizing Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The outcomes reveal that self-efficacy, work-life balance, and quality of work life have a positive and significant effect on employee performance. These outcomes recommend that employees’ confidence in their capabilities, balance between work and personal life, and supportive working conditions play an important role in enhancing performance. Therefore, organizations are encouraged to strengthen employee development programs and work policies to enhance sustainable employee performance.